Analysis of Learning Outcomes with TARL and CRT Approaches Through PBL and PJBL Models at SDN-SN Kebun Bunga 4 Banjarmasin - Alya Annida; Anisa Zahra; Hafiza Nurlatifa; Helda Fahrina; Yusniarti Yusniarti; Ali Rachman (Tunas: Jurnal Pendidikan Guru Sekolah Dasar, 2024)
Background: elementary school education plays a crucial role in shaping students' understanding of fundamental concepts, including an appreciation for cultural diversity. This research study aims to investigate the impact of the Teaching at the Right Level (TaRL) and Culturally Responsive Teaching (CRT) approaches on teaching cultural diversity to fourth-grade students in class IV B at SDN-SN Kebun Bunga 4. Method: applying a qualitative research method with a case study design, the study involved 16 students over three learning cycles. Results and Dıscussion: the applied instructional models included Problem-Based Learning (PBL) and Project-Based Learning (PjBL), which were integrated with the TaRL and CRT approaches to ensure the learning process was relevant to students' abilities and cultural backgrounds. The results revealed a significant improvement in the students' conceptual understanding, critical thinking skills, and practical abilities, increasing from 75% in the first cycle to 94% by the third cycle. Conclusion: the implementation of PBL and PjBL, adapted to individual learning levels and cultural relevance, proved effective in enhancing student outcomes, motivation, and participation. The study recommends the use of adaptive and culturally responsive approaches to strengthen student learning and character development.